Kematangan Berpikir dan Kesiapan Mengajar Guru SMA/SMK Berbasis Neurosains Terapan di Provinsi Kalimantan Utara - Abdul Rahman; Rizka Wahyuni (Patria Artha Journal of Nursing Science, 2026)
This study aims to determine the effect of thinking maturity of High School and Vocation Hight School teachers in North Kalimantan based on Applied Neuroscience and to determine the level of teaching readiness of SMA and SMK teachers in North Kalimantan based on Applied Neuroscience. The population in this study were all State High School and Vocational High School teachers in North Kalimantan Province, totaling 1,609 people. Data analysis used descriptive analysis of a quantitative approach based on Applied Neuroscience applications featuring Domination Graphs, Executive Brain Assessment Graphs, Thinking Graphs and Learning Graphs. The total number of teachers who carried out the Screening from Public High Schools and Vocational Schools in North Kalimantan Province was 1,609 people from 62 schools. Based on the research results and discussion, the authors draw conclusions in this study, based on the total percentage of teachers who are not ready to teach is very high, namely an average of 67%.